2008
DOI: 10.1007/s12038-008-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and molecular cloning of a new galactose-specific lectin from Bauhinia variegata seeds

Abstract: A new galactose-specific lectin was purified from seeds of a Caesalpinoideae plant, Bauhinia variegata, by affinity chromatography on lactose-agarose. Protein extracts haemagglutinated rabbit and human erythrocytes (native and treated with proteolytic enzymes), showing preference for rabbit blood treated with papain and trypsin. Among various carbohydrates tested, the lectin was best inhibited by D-galactose and its derivatives, especially lactose. SDS-PAGE showed that the lectin, named BVL, has a pattern simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…These enzymes act thru cleavage of certain membrane proteins, further exposing membrane carbohydrates comprising the glycocalyx of the erythrocyte membrane. This allows the lectin more access to surface carbohydrates, which might increase the hemagglutination titers [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes act thru cleavage of certain membrane proteins, further exposing membrane carbohydrates comprising the glycocalyx of the erythrocyte membrane. This allows the lectin more access to surface carbohydrates, which might increase the hemagglutination titers [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…This lectin, when used in skin wounds in mice, was responsible for the epithelium reconstruction and increased keratin deposition, indicating improved wound healing [4]. Partial results of this experiment showed no cytotoxicity for the lineages tested, when compared to the control groups.…”
Section: Methodsmentioning
confidence: 70%
“…The native lectin B. variegata (BVL) was extracted from seeds, according to the protocol described by Pinto et al [4]. The protein was characterized, quantified and tested for hemagglutination activity.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence heterogeneity was observed in one peptide D/S (T2/T2'), indicating that BBL preparations contain highly homologous isolectins. Similarly, the cloning and sequence of the B. variegata lectin gene have suggested that this protein could be encoded by a family of genes, which led to the identification of two isoforms (Pinto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%